How digital platforms influence young people's participation in governance and civic activities: evidence in Vietnam - Quynh, Nguyen Duy; Thanh, Nguyen Nghi (Asian journal of political science, 2025)
In this study, a group of 200 youth from Hanoi participated in COVID-19 volunteering campaigns in late 2021 to explore how the functionalities of digital platforms affect young people's participation in governance and civic activities in Vietnam. Using multivariate linear regression, six general areas of digital engagement were studied-In this case, this included Information access, mobilization and organization, engagement and dialogue, awareness and advocacy, educating and capacity building, networking and collaboration. All dimensions contributed significantly and positively to civic participation. Among them, engagement and dialogue (β = 0.146, p<0.01) and networking and collaboration (β = 0.196, p<0.001) were the strongest predictors. The model accounts for 50.5% of the variance in youth civic participation (adjusted R² = 0.490, F(6, 193) = 32.87, p<0.001). These findings furnish observable evidence from a non-Western context and provide practical implications to policymakers and civil society organizations working to amplify youth participation in civic processes through the use of digital tools.